Percutaneous Coronary Intervention (PCI) Strategies under Hemodynamic Support for Cardiogenic Shock: A Single-Center Experience with Two Patients - Talha Ahmed; Diljon Chahal; Ronson J. Madathil; David Kaczorowski; Anuj Gupta (Case Reports in Cardiology)
We describe two cases of profound cardiogenic shock complicating acute myocardial infarction (CSAMI) requiring mechanical circulatory support (MCS) with venoarterial extracorporeal membrane oxygenation (VA-ECMO) allowing complex, high-risk, and staged percutaneous interventions with successful decannulation but with unfortunate outcomes.